(untitled) (Eurasian Scientific Herald, 2023)
In this article, the chemical comparison of the chemical absorption of carbon dioxide in non-aqueous and aqueous systems was carried out. Investigation in non-aqueous systems 2-amino 2-methyl-1-propanol in aqueous medium used by MEA